PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. ICHIKO AGRO LESTARI KABUPATEN KUBU RAYA - B31110106, ARUM WENI YEKTI LESTARI (Jurnal Manajemen Update, 2016)
The title of this research is ?The Influence Of Organizational Experience towards Employers? Performance at PT. Ichiko Agro Lestari in Kubu Raya?. It aims to identify whether or not organizational experience influenced the employers? performance at PT. Ichiko Agro Lestari in Kubu Raya. In order to prove it, the research hypothesis was tested through multiple regression analysis by using SPSS. The result of the regression calculation simultaneously indicated that there had no significant effect between the independent variable (organizational culture) and dependant variable (employers? performance). Meanwhile, the result of partial regression calculation showed that only indicators such as put attention in details (X2) and team oriented (X5) which significantly affected employers? performance. In order words, the coefficient of determination rate (R2) was 0,083 (8,3%), meanwhile the remain (91,7%) was affected by other dependant variables which were not researched. Keyword : Employers? performance, organizational culturre